Analysis of the Impact of Employee Training and Knowledge Management Processes on the Performance of PT Vale Indonesia Tbk - Farras Rizki Darmawan; Didin Kristinawati (Cakrawala Repositori IMWI)
Employee training and knowledge management processes play an important role in improving organizational competitiveness and sustaining company performance, particularly in the mining industry, which faces market dynamics, occupational safety demands, and rapid technological transformation. PT Vale Indonesia Tbk, as a nickel mining company, strives to maintain employee performance in alignment with its vision, mission, and strategic objectives. Therefore, systematic training programs and structured knowledge management practices are required. This study aims to evaluate the effects of employee training and knowledge management processes on the performance of PT Vale Indonesia Tbk and to analyze the simultaneous effects of both factors as efforts to strengthen organizational performance. This phenomenon is examined using a quantitative method with a survey design, in which primary data are collected through structured questionnaires distributed to employees of PT Vale Indonesia Tbk. The research instrument is developed based on Dessler’s (2020) training theory, the Nonaka and Takeuchi SECI model for knowledge management processes, and the Kaplan and Norton Balanced Scorecard framework for measuring employee performance. The collected data are analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to empirically test the relationships and effects among variables. The expected results of this study are to identify the extent to which employee training and knowledge management processes influence employee performance, both partially and simultaneously, thereby providing a basis for improving human resource development programs and knowledge management practices at PT Vale Indonesia Tbk. This study is also expected to contribute theoretically to the development of human resource management and knowledge management process research.